RESEARCH ON HIGH PRECISION G-LOAD SIMULATION ALGORITHM OF DYNAMIC FLIGHT SIMULATOR - LUO Peng; HU RongHua; BAI JunLin; SHU Yang (Jixie qiangdu)
The G-load simulation principle and kinematic relationship of three-axis manned centrifuge are analyzed. The numerical method is used to solve the G-load simulation loading section, and the accurate calculation of the main arm speed of the overload simulation loading section is realized by simulation. The existence of the rotational speed solution of the main arm of the unloading section is analyzed, and the boundary of the rotational speed solution is clarified, which can also guide experimental designers to design the overload curve. Under the condition that the existence boundary of the solution is satisfied, the high precision numerical solution is obtained, and the G-load simulation accuracy of different methods is analyzed by combining pure Gz G-load simulation and three-direction G-load simulation.